The impact of fluence dependent 120 MeV Ag swift heavy ion irradiation on the changes in structural, electronic, and optical properties of AgInSe2 nano-crystalline thin films for optoelectronic applications. Issue 42 (30th July 2021) - Panda, R.; Khan, S. A.; Singh, U. P.; Naik, R.; Mishra, N. C.
Abstract : Swift heavy ion (SHI) irradiation in thin films significantly modifies the structure and related properties in a controlled manner. Abstract : Swift heavy ion (SHI) irradiation in thin films significantly modifies the structure and related properties in a controlled manner. In the present study, the 120 MeV Ag ion irradiation on AgInSe2 nanoparticle thin films prepared by the thermal evaporation method and the induced modifications in the structure and other properties are being discussed. The ion irradiation led to the suppression of GIXRD and Raman peaks with increasing ion fluence, which indicated amorphization of the AgInSe2 structure along the path of 120 MeV Ag ions. The Poisson's fitting of the ion fluence dependence of the normalized area under the GIXRD peak of AgInSe2 gave the radius of the ion track as 5.8 nm. Microstructural analysis using FESEM revealed a broad bi-modal distribution of particles with mean particle sizes of 67.5 nm and 159 nm in the pristine film. The ion irradiation led to the development of uniform particles on the film surface with a mean size of 36 nm at high ion fluences. The composition of the film was checked by the energy dispersive X-ray fluorescence (EDXRF) spectrometer. The UV-visible spectroscopy revealed the increase of the electronic bandgap of AgInSe2 films with an increase in ion fluence due to quantum confinement. The Hall measurement and EDXRF studies showed that the unirradiated and irradiated AgInSe2 films have n-type conductivity and vary with the ion fluence. The changes in the films were tuned with different ion fluence and are favorable for both optical and electronic applications.